Pelaksanaan Pengawasan dan Pengamatan oleh Hakim Pengawas dan Pengamat Dalam Pembinaan Narapidana di Pengadilan Negeri Denpasar - Ni Made Gita Iswariyani; I Nyoman Sujana; Diah Gayatri Sudibya (Jurnal Analogi Hukum, 2021)
The development of technology and Informatics in Indonesia has grown rapidly resulting in crime took place very quickly. A person who commits a criminal offence and has imposed a verdict running criminal prison called inmates. The time penalty Convicts still have human rights that are guaranteed by law. Law enforcement in ensuring human rights requires the role of law enforcement officers. Supervisory judges and observers’ one of the law enforcement officers who have the task of supervising and observing the Court ruling which has had the force of law. Monitoring and observations made Justice of the supervisors and Observers is useful as an evaluation against the Court ruling and also towards the overthrow of the criminal and the construction of the inmates. Formulation of the problem in this study is How supervisory arrangements and observations by judges and observers in the construction superintendent of convicts and how implementation of supervisory judges and observers in Denpasar District Court in the construction of the inmates. The type of research used in the writing of this thesis is the empirical legal research conducted with research in the field. Setting the execution of the duties of judges and observers of the trustees listed in the Judicial Authority law, the law of Criminal Procedure Law, and Supreme Court Circulars. Implementation of Supervisory Judges and observers has been already executed in accordance with the provisions but not yet running smoothly overall.